Public Technological Acceptance Of The Use on Artificial Intelligence as News Anchor in TV One Indonesia - Dwihadiah, Desideria Lumongga (SEMIOTIKA: Jurnal Komunikasi, 2024)
The development in communication technology, marked by innovation in artificial intelligence (AI), is entering a new phase in its application in mass media. One can be seen in using this technology as a news anchor on TV One AI. Because this is something new in Indonesia, public acceptance of this innovation needs to be studied further. This research uses a qualitative approach with a constructivist paradigm and descriptive methods. Technique. This research took a purposive sample by conducting semi-structured interviews with TV One AI news program viewers.The research findings show that when viewed from the audience reception model proposed by Hall, the audience is in a position of dominant hegemony and negotiation. These two positions show that the AI TV One news presenter can be accepted by the Indonesian people while considering the opposing sides that may become threats in the future.   It is hoped that the audience will be inquisitive about news programs using artificial intelligence in Indonesia, which will only partially eliminate the role of news anchors as journalists. Innovation is expected to be carried out gradually from one field to another as a form of introduction and use of artificial intelligence in the media realm in Indonesia.